The Planning, Design, and Delivery of Environmental Education and Interpretation in Ecotourism: A Case Study of Tiritiri Matangi Island - Cook, Georgia (Auckland University of Technology, 2024)
Ecotourism, focusing on sustainable and responsible travel in natural environments, aims to conserve ecosystems, benefit local communities, and promote environmental awareness through education. Central to the success of ecotourism ventures are the planning, design, and delivery of environmental education and interpretation programmes, as these play a pivotal role in enhancing visitor experiences, fostering environmental awareness, and promoting conservation efforts. In an era marked by ongoing environmental challenges, the need for environmental education and interpretation in ecotourism has become more pronounced than ever. However, a significant knowledge gap exists regarding the planning, design, and delivery of such programmes, especially within the context of New Zealand. This research aimed to bridge this gap by delving into these three elements in relation to environmental education and interpretation on Tiritiri Matangi Island, a renowned ecosanctuary situated near Auckland, New Zealand. This qualitative case study was underpinned by research philosophies encompassing the interpretive paradigm, a relativist ontology, and intersubjective epistemology. Through a comprehensive data collection process involving document analysis and semi-structured interviews with key stakeholders responsible for planning, designing, and delivering environmental education and interpretation on Tiritiri Matangi Island, the study sought to provide a holistic understanding of how these elements contribute to enriching the understanding and connection between visitors and the natural environment, as well as inspiring active engagement in conservation endeavours. The data were analysed and described using a thematic analysis technique to uncover recurring patterns and essential insights. The research uncovered the diverse historical facets that form the foundational backdrop for educational and interpretive experiences on Tiritiri Matangi Island. Additionally, the study shed light on the island’s strategic conservation plan, which encompasses five pivotal areas, all crucial to its overarching conservation, community engagement, and advocacy mission. Moreover, the findings revealed that the island’s environmental education and interpretation objectives were multifaceted, spanning four key dimensions directed at three different audiences to enhance visitors’ understanding and foster a deeper connection with the environment. The study sets out the island’s various environmental education and interpretation components, including guided tours, school education programmes, interpretive signage, and interactive displays. The results suggest that guided tours were designed to cater to a broad spectrum of visitors, establish links between the island’s conservation efforts and visitors’ daily lives, and offer relevance and immediacy. Furthermore, these tours were led by trained individuals with personal connections to the island and expertise in relevant subject matter, fostering a personalised and co-created experience for visitors. The findings also show that school education programmes target diverse school-age groups, focusing on nurturing environmental stewardship among children. Another outcome was that the island’s signage was meticulously designed to enrich the island experience by aiding in navigation, deepening botanical and ecological knowledge, enhancing avian understanding, serving as checklists, and motivating visitors to take conservation actions. Finally, the study reveals that the island employed nature immersion, multi-sensory experiences, storytelling, role modelling, and practical guidance to educate and inspire visitors, fostering a deep connection with nature and encouraging environmental stewardship beyond the site.